Instrumentation for the operating room : a photographic manual - Brooks Tighe, Shirley M. , 1939- (Elsevier Mosby, 2007)
Atlas of surgical instruments including those used for abdominal, general, endoscopic, vaginal and rectal, nervous system, peripheral vascular, cardiovascular, and thoracic, eye, ear, nose, and throat, orthopedic, oral, maxillary, and facial, plastic, and pediatric surgery.